2008
DOI: 10.1089/tmj.2008.0040
|View full text |Cite
|
Sign up to set email alerts
|

Videophone-Delivered Voice Therapy: A Comparative Analysis of Outcomes to Traditional Delivery for Adults with Parkinson’s Disease

Abstract: Individuals with idiopathic Parkinson's disease (IPD) usually develop a speech disorder characterized by reduced loudness, hoarse and breathy voice, monotony of pitch, short rushes of speech, and imprecise consonants. The inability to effectively communicate impairs their ability to function in society and quality of life. A successful program developed to improve speech in these individuals is the Lee Silverman Voice Treatment (LSVT). A critical component of this treatment is intense daily therapy for 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 15 publications
4
55
0
3
Order By: Relevance
“…Posttreatment gains were shown in both groups and were comparable, implying that voice treatment delivered through telepractice was as effective as in-person treatment for these participants. Tindall, Huebner, Stemple, and Kleinert (2008) examined voice treatment outcomes delivered through telepractice for a group of individuals with Parkinson's disease and compared those from a previously reported study (Ramig, Sapir, Fox, & Countryman, 2001) on individuals who were treated in in-person sessions. Twenty-four individuals diagnosed with idiopathic Parkinson's disease were provided the Lee Silverman Voice treatment (LSVT) approach through video phone calling.…”
Section: Telepractice and Voice Treatmentmentioning
confidence: 99%
“…Posttreatment gains were shown in both groups and were comparable, implying that voice treatment delivered through telepractice was as effective as in-person treatment for these participants. Tindall, Huebner, Stemple, and Kleinert (2008) examined voice treatment outcomes delivered through telepractice for a group of individuals with Parkinson's disease and compared those from a previously reported study (Ramig, Sapir, Fox, & Countryman, 2001) on individuals who were treated in in-person sessions. Twenty-four individuals diagnosed with idiopathic Parkinson's disease were provided the Lee Silverman Voice treatment (LSVT) approach through video phone calling.…”
Section: Telepractice and Voice Treatmentmentioning
confidence: 99%
“…Further support for the use of telepractice has been shown in studies comparing the outcomes of LSVT ® delivered remotely to the outcomes of traditional treatment delivered FTF. Investigators have reported post-treatment improvements achieved following remote LSVT ® and a similar magnitude of treatment effects was shown when compared with the FTF group (Constantinescu et al, 2011;Tindall et al, 2008;Theodoros et al, 2006). The benefits for such remote intensive voice treatment were that it may assist in reducing the effects of physical disability, and eliminates the need to travel to a hospital or clinic when transport and travel difficulties are encountered (Constantinescu et al, 2011;Tindall et al, 2008).…”
Section: Alternative Methods Of Service Delivery: Telepracticementioning
confidence: 96%
“…Studies have compared the accuracy of online assessment and the effectiveness of online treatment with FTF service across a range of areas of speech pathology practice. To date the finding have been very positive with no significant differences found between traditional and FTF methods of service delivery across populations with various speech, language and swallowing disorders (Brennan, Georgeadis, Baron, & Barker, 2004;Carey et al, 2010;Constantinescu, Theodoros, Russell, Ward, Wilson, & Wootton, 2010;Duffy, Werven & Aronson, 1997;Georgeadis, Brenna, Barker, & Baron, 2004;Lasker, Stierwalt, Spence, & Calvin-Root, 2010;Mashima et al, 2003;Theodoros & Russell, 2008, Tindall, Huebner, Stemple, & Kleinert, 2008Ward, Burns, Theodoros, & Russell, 2013;Ward, Burns, Theodoros, & Russell, 2014).…”
Section: Alternative Methods Of Service Delivery: Telepracticementioning
confidence: 99%
See 2 more Smart Citations